2022
DOI: 10.4102/safp.v64i1.5467
|View full text |Cite
|
Sign up to set email alerts
|

Retention of medical officers in the district health services of the Western Cape, South Africa: An exploratory descriptive qualitative study

Abstract: Background: An adequate health workforce is an essential building block of effective health systems. In South Africa, medical officers (MOs) are a key component of service delivery in district health services. The Stellenbosch University Family Physician Research Network in the Western Cape identified that retention of MOs was a key issue. The aim of this study was to explore the factors that influence the retention of MOs in public sector district health services in the Western Cape, South Africa.Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Following this survey, a descriptive exploratory qualitative study attempted to unpack what factors were influencing the rating of the facility. 20 This study suggested that teamwork, support, and supervision were critical. Being part of a cohesive and caring clinical team was important, as well as having access to support and supervision when needed from senior colleagues.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Following this survey, a descriptive exploratory qualitative study attempted to unpack what factors were influencing the rating of the facility. 20 This study suggested that teamwork, support, and supervision were critical. Being part of a cohesive and caring clinical team was important, as well as having access to support and supervision when needed from senior colleagues.…”
Section: Discussionmentioning
confidence: 88%
“…The survey pointed towards useful issues that could be explored further in the qualitative study that came afterwards. 20 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations